In situ X-ray diffraction studies on the piezoelectric response of PZT thin films - Davydok, A.; Cornelius, T. W.; Mocuta, C.; Lima, E. C.; Araujo, E. B. [UNESP]; Thomas, O. (Elsevier B.V., 2016)
Piezoelectric properties of randomly oriented self-polarized PbZr0.50Ti0.50O3 (PZT) thin films were investigated using in situ synchrotron X-ray diffraction. Possibilities for investigating the piezoelectric effect using microsized hard X-ray beams are demonstrated and perspectives for future dynamical measurements on PZT samples with variety of compositions and thicknesses are given. Studies performed on the crystalline [100, 110] directions evidenced piezoelectric anisotropy. The piezoelectric coefficient d(33) was calculated in terms of the lab reference frame (d(perp)) and found to be two times larger along the [100] direction than along the [110] direction. The absolute values for the d(perp) amount to 120 and 230 pm/V being in good agreement with experimental and theoretical values found in literature for bulk PZT ceramics. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Piezoeffect; X-ray diffraction; Thin film; Anisotropy; In-situ experiment